Compliance with disclosure requirements under IFRS 3 of companies trading at Prague Stock Exchange - Taisia Nistorenco (European Financial and Accounting Journal, 2019)
This article analyses compliance with information disclosure requirements under IFRS 3 Business Combinations in 23 companies trading at Prague Stock Exchange. The analysis was performed with the use of publicly available data contained in annual reports of the companies. Beyond quantification of the level of compliance, the research explores which factors affect diligence in following IFRS 3 disclosure requirements, specifically the company size, history of trading on the stock exchange, ownership structure and the acquisition price paid. The literature review also focuses on aspects with a potential to influence the level of diligence in areas of disclosure and consequences of infringing the disclosure rules. The paper concludes that the level of compliance can be considered average and in some cases unsatisfactory, while the company size and longer history of trading on PSE are positively correlated with the quality of disclosure.
Keywords: M41; G30; 650; IFRS 3 Business Combinations; Disclosure; Czech Publicly Traded Companies; Prague Stock Exchange